Platelet-rich plasma versus hyaluronic acid in knee osteoarthritis: A meta-analysis with the consistent ratio of injection. (2nd January 2020) - Wu, Qipeng; Luo, Xuefen; Xiong, Yuan; Liu, Guohui; Wang, Junwen; Chen, Xi; Mi, Bobin
Osteoarthritis (OA) is an extremely common form of chronic joint disease which can affect the knees and other joints of older adults, leading to debilitating disability in the knee and consequent reduction in quality of life. Intra-articular platelet-rich plasma (PRP) or hyaluronic acid (HA) injections are effective for maintaining long-term beneficial effects without increasing the risk of intra-articular infection. However, few studies have compared the relative value of HA and PRP for OA treatment. PRP is more effective than HA for OA treatment in recent studies of this topic. We systematically searched Medline, SpringerLink, Embase, Pubmed, Clinical Trials.gov, the Cochrane Library, and OVID for all articles published through May 2018. Any study was included that compared the effect of HA and PRP (consistent treatment cycle and frequency of injection) on patient's pain levels and functionality improvements. Review Manager 5.3 was used to analyze data regarding these two primary outcomes. We included 10 total studies in the present meta-analysis. International Knee Documentation Committee (IKDC; MD: 10.37, 95% confidence interval (CI): 9.13 to 11.62, p < 0.00001), Western Ontario and MacMaster Universities Osteoarthritis Index (WOMAC; MD: −20.69, 95% CI: −24.50 to −16.89, p < 0.00001, I 2 = 94%), and Visual Analogue Scale (VAS; MD: −1.50, 95% CI: −1.61 to −1.38, p < 0.00001, I 2 = 90%) differed significantly between the PRP and HA groups. Knee Osteoarthritis Outcome Scores (KOOSs) did not differ significantly ( χ 2 = 23.53, I 2 = 41%, p = 0.11). Our hypothesis appears not to be confirmed because PRP and HA did not differ significantly with respect to KOOS score. However, the IKDC, WOMAC, and VAS scores differed significantly. Thus, based on the current evidence, PRP appears to be better than HA at achieving pain relief and self-reported functional improvement. Ia, meta-analyses of randomized clinical trials.